Smart online electrical billing management system (SOEBIMS) using GSM - Wong, Ying Yin (2012)
Nowadays the billing system integrated with smart meter is used by staffs, residents and those who use electricity to retrieve the price rate and meter value of power consumption. There are several billing system integrated with smart meter invented in Italy, Sweden, UK, USA and so on. However, the current metering system in Malaysia is not capable to measure variable time price and it is gradually replaced by digital or smart meters. The purpose of this study is to develop a prototype of Smart Online Electrical Billing Management System (SOEBIMS) using GSM. SOEBIMS is an online web application as it can reduce human errors and save time to key in the data from keyboard. SOEBIMS helps to retrieve the real time meter value via GSM and send it to customer’s mobile phone through GSM. The staffs allow modifying the variable package price in specific duration. The administrator can analyze the customer’s power consumption data and generate the report from the data online. The prototype is developed using waterfall model as the prototype can be implement and develop by followed the sequential phases. The prototype will be able to introduce the billing system to the customers, get the power consumption data from smart meter, keep the data in centralized database and generate the report. It will help the user to access the data and report easily through online.